TRIP13 regulates DNA repair pathway choice through REV7 conformational change - Clairmont, Connor S; Sarangi, Prabha; Ponnienselvan, Karthikeyan; Galli, Lucas D; Csete, Isabelle; Moreau, Lisa; Adelmant, Guillaume; Chowdhury, Dipanjan; Marto, Jarrod A; D'Andrea, Alan D (Nature cell biology, 2020)
DNA double-strand breaks (DSBs) are repaired through homology-directed repair (HDR) or non-homologous end joining (NHEJ). BRCA1/2-deficient cancer cells cannot perform HDR, conferring sensitivity to poly(ADP-ribose) polymerase inhibitors (PARPi). However, concomitant loss of the pro-NHEJ factors 53BP1, RIF1, REV7-Shieldin (SHLD1-3) or CST-DNA polymerase alpha (Pol-α) in BRCA1-deficient cells restores HDR and PARPi resistance. Here, we identify the TRIP13 ATPase as a negative regulator of REV7. We show that REV7 exists in active 'closed' and inactive 'open' conformations, and TRIP13 catalyses the inactivating conformational change, thereby dissociating REV7-Shieldin to promote HDR. TRIP13 similarly disassembles the REV7-REV3 translesion synthesis (TLS) complex, a component of the Fanconi anaemia pathway, inhibiting error-prone replicative lesion bypass and interstrand crosslink repair. Importantly, TRIP13 overexpression is common in BRCA1-deficient cancers, confers PARPi resistance and correlates with poor prognosis. Thus, TRIP13 emerges as an important regulator of DNA repair pathway choice-promoting HDR, while suppressing NHEJ and TLS.